Extraction of Cu(Ii), Fe(Iii), Zn(Ii), and Mn(Ii) from Aqueous Solutions with Ionic Liquid r4ncy - Navarro-Donoso, P; Vargas-Riquelme, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The leaching of copper ores produces a rich solution with metal interferences. In this context, Fe(III), Zn(II), and Mn(II) are three metals contained in industrial copper-rich solutions in high quantities and eventually can be co-extracted with the copper. The purpose of the current study was to determine the feasibly of solvent extraction with the use of ionic liquid methyltrioctyl/decylammonium bis (2,4,4-trimethylpentyl)phosphinate (R4NCy) as an extractant of Cu(II) in the presence of Fe(III), Zn(II), and Mn(II). In general terms, the results showed a high single extraction efficiency of all the metals under study. In the case of Fe(III) and Zn(II), the extraction was close to 100%. On the contrary, the stripping efficiency was poor to Fe(III) and discrete to Zn(II), but very high to Cu(II) and Mn(II). Finally, the findings of this study suggest that the ionic liquid R4NCy is feasible for the pre-treatment of the copper solvent extraction process to remove metal impurities such as Fe(III) and Zn(II). © 2021 by the authors. Licensee MDPI, Basel, Switzerland.